Diabetes health-beliefs, self-care practices and glycaemic control among Malaysian young adults with diabetes - Aris, Aishairma; Blake, Holly; Adams, Gary (Unidade de Investigação em Ciências da Saúde - Enfermagem da Escola Superior de Enfermagem de Coimbra, 2011)
Self-care practices and glycaemic control remain suboptimal among young adults with diabetes. One of the known factors to influence self-care behaviours is health beliefs. Targeting health beliefs through diabetes education facilitates individual’s diabetes self-care behaviours. Studies investigating health beliefs of young adults with diabetes are limited, however, to educational settings and include mixed-age participant groups. Knowledge about the health beliefs, self-care practices and glycaemic control specifically among Malaysian young adults with diabetes is lacking.